The Effect of Feedwater Heaters Operation Schemes to a 200 MW Steam Power Plant Heat Rate Using Cycle-Tempo Software - Adi Apriyanto Wijaya; Budi Utomo Kukuh Widodo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
There are several ways to improve performance of Rankine cycle which is implemented at steam power plant, regenerative feedwater heating is one of the methods. Some failures in closed feedwater heaters such as, water leak through manhole and tube leakage may happen during operation of the plant. Repairing such failures may take some period of time and must shut off the operation of the feedwater heaters. Further study is needed to evaluate the effect of closed feedwater heater in off-service condition against the steam power plant’s performance. This study varies off-service condition of closed feedwater heaters applying thermodynamics analysis and modeled through Cycle-Tempo software. There are 12 possible feedwater heater operation schemes. Based on the heat balance and equipment design of a 200 MW Steam Power Plant at Jakarta-Indonesia, this study concluded that the NPHR might increase as much as 0.96% and 0.39% due to the off-service of any HPH and the off-service of any LPH respectively. Schemes of 2 off-service feedwater heaters summed up with 1.37% increase of NPHR.